2009
DOI: 10.1007/s00246-008-9375-0
|View full text |Cite
|
Sign up to set email alerts
|

Staff Radiation Doses in Interventional Cardiology: Correlation With Patient Exposure

Abstract: In pediatric interventional cardiology, cardiologists need to stay closer to the patient than during adult catheterization, and the use of biplane systems increases the scatter radiation. Occupational radiation risk is rather high, and estimation of lens doses becomes necessary. Deriving factors for assessing these doses from the patient doses displayed in catheterization laboratories can help in preserving staff radiation safety. A biplane X-ray system and polymethylmethacrylate plates of 4 to 20 cm to simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
1
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 17 publications
0
35
1
4
Order By: Relevance
“…Others have shown that scatter dose rate is proportional to patient skin dose rate (7). Because the shape of the phantom does not accurately reflect that of a real patient (let alone a range of patients), the magnitude of the scatter measurements cannot be considered to accurately reflect clinical practice.…”
Section: Positions F and H)mentioning
confidence: 98%
See 1 more Smart Citation
“…Others have shown that scatter dose rate is proportional to patient skin dose rate (7). Because the shape of the phantom does not accurately reflect that of a real patient (let alone a range of patients), the magnitude of the scatter measurements cannot be considered to accurately reflect clinical practice.…”
Section: Positions F and H)mentioning
confidence: 98%
“…To help minimize radiation dose, all persons working in interventional x-ray rooms are required to wear lead-equivalent radiation protection garments. Although these garments are effective at stopping radiation, a person's arms, head, and neck (without protective collar) are generally unprotected (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Nevertheless, continuing exposure and higher doses can promote a higher risk that may still be unknown. 26,27 Limitations of the study The present study had several limitations that must be considered. This analysis was conducted in only one centre with a small patient sample.…”
Section: Discussionmentioning
confidence: 93%
“…De plus, seuls 31 % 164 C. Bolomey et al : Radioprotection 51(3), 163-170 (2016) des opérateurs en radiologie interventionnelle portent systéma-tiquement des lunettes de protection (Vanhavere et al, 2012). En radiologie interventionnelle pédiatrique, l'exposition de l'opérateur peut être d'autant plus conséquente du fait de l'utilisation fréquente d'un système de radioscopie biplan et de la plus grande proximité du médecin avec le patient (Vaño et al, 2009).…”
Section: Introductionunclassified